2021
DOI: 10.1073/pnas.2003193118
|View full text |Cite|
|
Sign up to set email alerts
|

Mdm2 phosphorylation by Akt regulates the p53 response to oxidative stress to promote cell proliferation and tumorigenesis

Abstract: We have shown previously that phosphorylation of Mdm2 by ATM and c-Abl regulates Mdm2-p53 signaling and alters the effects of DNA damage in mice, including bone marrow failure and tumorigenesis induced by ionizing radiation. Here, we examine the physiological effects of Mdm2 phosphorylation by Akt, another DNA damage effector kinase. Surprisingly, Akt phosphorylation of Mdm2 does not alter the p53-mediated effects of ionizing radiation in cells or mice but regulates the p53 response to oxidative stress. Akt ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
61
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(63 citation statements)
references
References 50 publications
1
61
1
Order By: Relevance
“…This search accurately retrieved 451 annotated target genes, which referred to 444 unique Entrez Gene IDs assigned to 417 protein coding genes, 24 lncRNAs, 2 pseudogenes, and 1 TEC, and distributed throughout all chromosomes ( Supplementary Info S1 ). Surprisingly, only 4 among the 444 unique Entrez Gene IDs (about 1%) were annotated to oxidative stress GO term (GO:0006979): CHD6 (chromatin remodeler and key regulator of the oxidative DNA damage response) [ 32 ], RBM11 (oxidative stress-responsive splicing regulator) [ 33 ], MDM2 (protooncogene and regulator of the p53 response to oxidative stress) [ 34 , 35 ], and SOD2 (mitochondrial MnSOD enzyme playing a key antioxidative role in the lung) [ 36 ].…”
Section: Resultsmentioning
confidence: 99%
“…This search accurately retrieved 451 annotated target genes, which referred to 444 unique Entrez Gene IDs assigned to 417 protein coding genes, 24 lncRNAs, 2 pseudogenes, and 1 TEC, and distributed throughout all chromosomes ( Supplementary Info S1 ). Surprisingly, only 4 among the 444 unique Entrez Gene IDs (about 1%) were annotated to oxidative stress GO term (GO:0006979): CHD6 (chromatin remodeler and key regulator of the oxidative DNA damage response) [ 32 ], RBM11 (oxidative stress-responsive splicing regulator) [ 33 ], MDM2 (protooncogene and regulator of the p53 response to oxidative stress) [ 34 , 35 ], and SOD2 (mitochondrial MnSOD enzyme playing a key antioxidative role in the lung) [ 36 ].…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, Akt can regulate p53 stability by phosphorylating MDM2 at specific serine residues (166, 183, or 188) to facilitate MDM2 translocation into the nucleus and reduce p53-dependent gene transactivation, and increase the degradation of p53 [ 65 , 66 , 67 ]. Exemplifying the importance of these residues, in murine HCC models, the generation of mice with Ser 183 replaced by alanine in MDM2 reduced HCC load, suggesting that the absence of Ser 183 phosphorylation sensitizes cells to oxidative stress-induced senescence and ultimately HCC progression [ 68 ].…”
Section: The Pi3k/akt/mtor Pathwaymentioning
confidence: 99%
“…Third, AKT promotes p53 degradation by directly phosphorylating MDM2 on Ser166 and/or Ser186, which facilitates the nuclear translocation of MDM2 ( Mayo and Donner, 2001 ; Zhou et al, 2001 ) and stabilizes it ( Feng et al, 2004 ). Particularly, in vivo studies using Mdm2 S183A mice recently showed that AKT phosphorylation of Mdm2 at Ser183 (the murine equivalent of human Ser186) suppresses p53-mediated senescence, facilitates ROS-induced tumorigenesis, and has no effects on DNA damage response induced by radiation ( Chibaya et al, 2021 ). Moreover, AKT also regulates phosphorylation of MDM4, which complexes with MDM2 to degrade p53, at Ser367 to stabilize it and consequently inactivate p53 ( Lopez-Pajares et al, 2008 ; Pellegrino et al, 2014 ).…”
Section: Introduction: the Tumor Suppressor P53mentioning
confidence: 99%